MEF2C Common Genetic Variation Is Associated With Different Aspects of Cognition in Non-Hispanic White and Caribbean Hispanic Non-demented Older Adults - Sunderaraman, Preeti; Cosentino, Stephanie; Schupf, Nicole; Manly, Jennifer; Gu, Yian; Barral, Sandra (Frontiers in Genetics, 2021)
Objectives: Myocyte Enhancer Factor 2C (MEF2C) is identified as a candidate gene contributing to the risk of developing Alzheimer’s disease. However, little is known about whether MEF2C plays a role in specific aspects of cognition among older adults. The current study investigated the association of common variants in the MEF2C gene with four cognitive domains including memory, visuospatial functioning, processing speed and language among non-demented individuals. Method: Participants from two ethnic groups, Non-Hispanic White (NHW; n= 537) and Caribbean Hispanic (CH; n=1,197) from the Washington Heights-Inwood Community Aging Project (WHICAP) study, were included. Genetic association analyses using WHICAP imputed genome-wide data (GWAS) were conducted for the various cognition domains. Results: Single nucleotide polymorphisms (SNP) variants in the MEF2C gene showed nominally significant associations in all cognitive domains but for different SNPs across both the ethnic groups. In NHW participants, the strongest associations were present for memory (rs302484), language (rs619584), processing speed (rs13159808), and visuospatial functioning (several SNPs). In CH, strongest associations were observed for memory (rs34822815), processing speed (rs304141), visuospatial functioning (rs10066711 and rs10038371), and language (rs304153). Discussion: MEF2C variant-cognitive associations shed light on an apparent role for MEF2C in both memory and non-memory aspects of cognition in individuals from NHW and CH ancestries. However, the little overlap in the specific SNP-cognition associations in CH versus NHW highlights the differences in genetic architectural variations among those from different ancestries that should be considered while studying the MEF2C gene.